Implementasi Kebijakan Peningkatan Partisipasi Masyarakat Dalam Perancangan Undang-Undang (SIMAS PUU) - Adani, Puteri Shabrina; Asropi, Asropi; Widjayanti, Arifiani (Jurnal Administrasi dan Kebijakan Publik, 2023)
The application of the e-government system is carried out to facilitate and speed up services to the community. This research focuses on answering the implementation of the regulations of the Head of the DPR RI Expertise Agency regarding the management of public participation in drafting laws that have not run optimally. A descriptive qualitative approach is used in research that takes place at the Center for Drafting of Laws, the Expertise Body of the DPR RI. Van Meter and Van Horn's theory focuses on policy standards and objectives, resources, communication between implementing agencies, implementing organizational characteristics, implementing attitudes, and the social, economic, and political environment that can be linked to the external environment. The results of this study are that all aspects of the policy implementation model from Van Meter and Van Horn have not been achieved as a measure of the success of implementing the SIMAS PUU application due to minimal human resources, financial support, and enthusiasm from the external environment. Therefore, it can be concluded that the implementation of the SIMAS PUU application has not run optimally.